Uterine Angioleiomyoma with Atypia, Raised CA-125 Levels, and Pseudo-Meigs Syndrome: An Alarming Presentation - Sunitha Thomas; Laxmi Radhakrishnan; Latha Abraham; Anna Matthai (Case Reports in Pathology)
Angioleiomyomas are benign mesenchymal tumours commonly occurring in the subcutis of extremities. They are typically composed of interlacing fascicles of smooth muscle cells with intersecting vascular channels. Angioleiomyomas of the uterus are rare with only very few case reports available in literature. Herein, we report a case of this rare entity in a 47-year-old woman owing to its highly unusual features of cellular atypia, raised CA-125 levels, and pseudo Meigs syndrome.